2014
DOI: 10.1007/s00289-014-1269-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of antimicrobial PCL/nanoclay nanocomposite films with enhanced mechanical and water vapor barrier properties for packaging applications

Abstract: Biodegradable PCL-based nanocomposites were successfully prepared by melt mixing of the poly(e-caprolactone) with two organo-modified Algerian montmorillonites by the cation exchange reactions with two quaternary ammonium surfactants, namely hexadecyl trimethyl ammonium chloride (OMMT1) and hexadecyl pyridinium chloride (OMMT2), with the aim to elaborate antimicrobial PCL/nanoclay composite films with enhanced properties for food packaging applications. PCL-based nanocomposite films containing either OMMT1 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 68 publications
(77 reference statements)
3
46
0
Order By: Relevance
“…The increased Ra and Rms values correspond to the morphological change observed in the SEM images (Diaconu et al 2008). From the FTIR spectra, the incorporation of Cloisite 30B in the PCL matrix could be confirmed (Yahiaoui et al 2015). From the results of water uptake studies, it can be observed that the membranes do not show any significant change upon increasing filler addition.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The increased Ra and Rms values correspond to the morphological change observed in the SEM images (Diaconu et al 2008). From the FTIR spectra, the incorporation of Cloisite 30B in the PCL matrix could be confirmed (Yahiaoui et al 2015). From the results of water uptake studies, it can be observed that the membranes do not show any significant change upon increasing filler addition.…”
Section: Discussionmentioning
confidence: 94%
“…The antimicrobial activity of the PCL/clay composite has been linked to the migration of free ammonium surfactant from PCL composite film to the culture media, because intercalation of the PCL into the clay galleries could cause the release of the ammonium surfactant associated with the negatively charged part of the clay (Ferfera‐Harrar et al 2014; Malachová et al 2009). Hence, microbicidal activity of the composite can be considered to be related to the ammonium surfactants of the organoclay (Eudy 1981; Sauvet et al 2000; Senuma et al 1989) which can have activity against microorganisms due to their ability to interact with cell membrane (Yahiaoui et al 2015). Under physiological conditions, bacterial cell wall has a negative charge due to the presence of functional groups, such as carboxylates, present in lipoproteins at the surface (Breen et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial PCL-based bio-nanocomposites using quaternary ammonium modified montmorillonites (OMMTs) have been prepared for packaging [210]. The performance of the composite films against Staphylococcus aureus (Gram positive) and Escherichia coli (Gram negative) have been evaluated from the number density of bacteria in the sample.…”
Section: Food Packagingmentioning
confidence: 99%
“…When 7.5 log cells of E. coli O157:H7 were inoculated in orange juice, a significant reduction in E. coli cell population was observed to 3.5 log units after 72 h when PLA/nisin was used whereas the control had declined to about 6 log units. These intrinsic deficiencies are generally removed using nanotechnology by dispersing nanometer dimension particle in polymer matrix, so called 'nanocomposite' [210,212]. The agar diffusion test was investigated to monitor antimicrobial activity of PLA/nisin film for solid foods packaging.…”
Section: Food Packagingmentioning
confidence: 99%
“…Many publications were related to block copolymer-based nanocomposites with tailored dispersion of nanofillers [6][7][8][9]. Montmorillonite (MMT), known as clay, is toxicologically safe nanofiller with layered silicates structure [10], while can bring a remarkable improvement in physical, mechanical [11] and barrier properties [12][13][14] of most polymers, even at very low concentration. Like other nanofiller, such as grapheme [15], carbon nanotube [16], the state of exfoliation, concentration and orientation of nanoclay, as well as the structure of polymer matrix are believed to be the key factor in achieving optimum properties of the nanocomposites [17,18].…”
Section: Introductionmentioning
confidence: 99%